"Aging males" symptoms and general health of adult males: a cross-sectional study. (2nd April 2016) - Yuen, John W.; Ng, Chi-Fai; Chiu, Peter Ka Fung; Teoh, Jeremy Yuen Chun; Yee, CH
Abstract: A cross-sectional study was conducted to explore the prevalence and severity of health-related complaints perceived by adult males of Hong Kong by using the Hong Kong Traditional Chinese versions of the Aging males' symptoms (AMS) scale and the 5-dimensional and 3-level European Quality of life (EQ-5D-3L) questionnaire. A total of 825 adult males aged 40 years or above were surveyed, and observed that 80% of the population was living with little-to-mild levels of aging symptoms with mean total scores ranged between 26.02 ± 7.91 and 32.99 ± 7.91 in different age groups. Such symptoms were correlated with age, especially for the somato-vegetative and sexual symptoms. The most severe AMS symptoms were observed in the oldest age group at 70 years or above, with 76%, 34% and 70% living with moderate-to-severe levels of somato-vegetative, psychological and sexual symptoms, respectively. The result was highly correlated with the EQ-5D-3L questionnaire. Secondly, the Hong Kong Aging males' symptoms (AMS) scale was shown to have good reliability with test–retest coefficient at 0.79 (ranged 0.66–0.87) and Cronbach's alpha coefficient at 0.88 (ranged 0.70–0.84). In summary, the population of Hong Kong male adults was commonly living with little-to-mild levels of aging symptoms, whereas their severity was correlated with age.